2020
DOI: 10.31967/relasi.v16i1.347
|View full text |Cite
|
Sign up to set email alerts
|

Satifaction As Intervening For The Antecedents Of Intention To Revisit: Marine Tourism Context In East Java

Abstract: The purpose of this study was to identify the effect of brand experience and service quality on intention to revisit with satisfaction as a mediating variable in the marine tourism in Indonesia. A total of 241 worthwhile questionaires were collected to be used to examine the structural model and the measurement using PLS path modelling analysis. This research was conducted in several coastal tourism objects in East Java, which were emphasized on the north coast of East Java. This study found that service quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 56 publications
(159 reference statements)
0
4
0
Order By: Relevance
“…The findings show that satisfaction and loyalty are important variables within coastal and marine tourism (Fianto, 2020;Prayag, 2012;Pestana et al, 2019;Fianto, 2020;Sangpikul, 2018). However, the present study contributes to the scientific literature because it links the segments with satisfaction and loyalty in a coastal city.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The findings show that satisfaction and loyalty are important variables within coastal and marine tourism (Fianto, 2020;Prayag, 2012;Pestana et al, 2019;Fianto, 2020;Sangpikul, 2018). However, the present study contributes to the scientific literature because it links the segments with satisfaction and loyalty in a coastal city.…”
Section: Discussionmentioning
confidence: 54%
“…Lam-González, León, and De León (2020) found that affective feelings towards the nautical destination were an important antecedent of satisfaction in nautical tourists. In a recent study, Fianto (2020) found that service quality has a significant effect on the intention to revisit a destination. The scholars also found that the experience of the brand had a significant influence on the intention of visiting the site again.…”
Section: Satisfaction and Loyalty In Coastal Citiesmentioning
confidence: 99%
“…Rice and Khanin [ 32 ] identified that repeated visits to tourist destinations in the United States were influenced by satisfaction and motivations (push/pull), being the influence of push factors the strongest, and acting both as mediator variables. Likewise, Fianto [ 33 ] argued that the quality of service and brand experience significantly affected visitors’ intention to return to a place, acting visitors’ satisfaction at the same time as a mediator of the relationship between market experience and the revisit intention.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In another study, Prayag [38] predicted behavioral loyalty and highlighted three aspects that improve the intentions to return to a destination: natural environment, reputation, and friendliness of people. Fianto [39] identified that the quality of the service has a significant effect on the intention to revisit a destination. Additionally, the experience of the brand was also found to have a significant influence on the intention to revisit.…”
Section: Loyalty In Coastal Destinationsmentioning
confidence: 99%